Psalterium Demetrii Sinaitici et Folia Medicinalia (Monasterii sanctae Catharinae codex slavicus NF 3): NF3_MedFol (2021)
After the 2012 facsimile edition this volume contains critical editions of Demetrius' Psalter and the Medical Folia preserved in it in Cyrillic transliteration. Besides treatises on textual criticism and the lexical peculiarities of the Psalter, the introductory part also deals with Demetrius and his additions as well as the provenance and content of the Medical Folia (each with translation and glossary); it concludes with a description of the images on which the investigations were based and that are added on a flash drive as well as the spectroscopic analysis of the manuscript. Editio critica: https://e-book.fwf.ac.at/o:1578 NF3_Beschreibung Bildmaterial: https://e-book.fwf.ac.at/o:1582 NF3_Dokumentaion: https://e-book.fwf.ac.at/o:1583 NF3_MedFol: https://e-book.fwf.ac.at/o:1584 NF3_PsDem_rgb: https://e-book.fwf.ac.at/o:1585 NF3_PsDem_sectral: https://e-book.fwf.ac.at/o:1586